Effect of Silicon, Titanium, and Zirconium Ion Implantation on NiTi Biocompatibility - L. L. Meisner; A. I. Lotkov; V. A. Matveeva; L. V. Artemieva; S. N. Meisner; A. L. Matveev (Advances in Materials Science and Engineering)
The objective of the work was to study the effect of high-dose ion implantation (HDII) of NiTi surface layers with Si Ti, or Zr, on the NiTi biocompatibility. The biocompatibility was judged from the intensity and peculiarities of proliferation of mesenchymal stem cells (MSCs) on the NiTi specimen surfaces treated by special mechanical, electrochemical, and HDII methods and differing in chemical composition, morphology, and roughness. It is shown that the ion-implanted NiTi specimens are nontoxic to rat MSCs. When cultivated with the test materials or on their surfaces, the MSCs retain the viability, adhesion, morphology, and capability for proliferation in vitro, as evidenced by cell counting in a Goryaev chamber, MTT test, flow cytometry, and light and fluorescence microscopy. The unimplanted NiTi specimens fail to stimulate MSC proliferation, and this allows the assumption of bioinertness of their surface layers. Conversely, the ion-implanted NiTi specimens reveal properties favorable for MSC proliferation on their surface.